Women and gender in Islam: Historical roots of a modern debate - Ahmed, Leila (Yale University Press., 1992)
Explores the historical roots of the debate about women in Islamic societies by tracing the developments in Islamic discourses on women and gender up to the present. The book describes the gender systems in place in the Middle East both before and after the rise of Islam.
Keywords: 1800-1899; 1900-1999; approches et analyses; asie; cours; cycles supérieurs; discipline; fem1000; fem7000; femmes* musulmanes; féminisme islamique; genre; histoire; identités LGBTQIA2+; islam; lit3220; moyen-âge; orient; premier cycle; périodes historiques; rapports de domination; rapports sociaux de sexe; religion; ressource en ligne; régions géographiques; science des religions; sciences humaines; sexisme; sociologie; syrie; systèmes d'oppressions; thématiques; théologie; voiles islamiques

Unruly women: The politics of social and sexual control in the old South - Bynum, Victoria E. (University of North Carolina Press, 1992)
In this richly detailed and imaginatively researched study, Victoria Bynum investigates "unruly" women in central North Carolina before and during the Civil War. Analyzing the complex and interrelated impact of gender, race, class, and region on the lives of black and white women, she shows how their diverse experiences and behavior reflected and influenced the changing social order and political economy of the state and region. Her work expands our knowledge of black and white women by studying them outside the plantation setting.Bynum searched local and state court records, public documents, and manuscript collections to locate and document the lives of these otherwise ordinary, obscure women. Some appeared in court as abused, sometimes abusive, wives, as victims and sometimes perpetrators of violent assaults, or as participants in illicit, interracial relationships. During the Civil War, women frequently were cited for theft, trespassing, or rioting, usually in an effort to gain goods made scarce by war. Some women were charged with harboring evaders or deserters of the Confederacy, an act that reflected their conviction that the Confederacy was destroying them.These politically powerless unruly women threatened to disrupt the underlying social structure of the Old South, which depended upon the services and cooperation of all women. Bynum examines the effects of women's social and sexual behavior on the dominant society and shows the ways in which power flowed between the private and public spheres. Whether wives or unmarried, enslaved or free, women were active agents of the society's ordering and dissolution.
Disponible en livre numérique et en format imprimé.
Keywords: 1800-1899; amériques; approches et analyses; civil war; cours; discipline; féminisme matérialiste; his4443; histoire; histoire des femmes*; histoire et politique; intersectionnalité; premier cycle; périodes historiques; racisme; rapports sociaux de sexe; ressource en ligne; régions géographiques; sciences humaines; sexualité; systèmes d'oppressions; thématiques; violences; états-unis

Rapports sociaux de sexe et conceptualisation sociologique - Daune-Richard, Anne-Marie; Devreux, Anne-Marie (Recherches féministes, 1992)
La déconstruction d'une conception biocentriste des sexes en sociologie et la mise en évidence, par les travaux féministes des années 1970, de l'existence d'un système des sexes a ouvert la voie à l'élaboration d'une théorie des rapports sociaux entre les sexes. Cette théorie critique et redéfinit certains concepts clés (travail, production, mobilité), déplace les frontières disciplinaires (sociologie du travail, sociologie de la famille), en même temps qu'elle élargit les débats sur des thèmes sociologiques fondamentaux : relations entre rapport social et catégorisation sociale, reproduction sociale et changement, structures et acteurs et actrices, pratiques sociales et représentations. Aujourd'hui, ce travail de théorisation se poursuit à travers l'élaboration d'outils d'analyse sociologique (de concepts opératoires) susceptibles de rendre compte de la dynamique qui est le propre d'un rapport social, le rapport social entre les sexes en particulier.
http://www.erudit.org/en/journals/rf/1900-v1-n1-rf1646/057697ar/abstract/
Keywords: 1900-1999; approches et analyses; cours; cycles supérieurs; discipline; europe; famille; fem1000; fem9000; france; premier cycle; périodes historiques; rapports sociaux de sexe; ressource en ligne; régions géographiques; sciences humaines; sociologie; thématiques; travail

Rethinking masculinity: philosophical explorations in light of feminism - May, Larry; Strikwerda, Robert A.; Hopkins, Patrick D. (Rowman & Littlefield, 1992)
Are men naturally aggressive? What makes a good father? How can men form intimate friendships? In the new edition of this popular anthology, seventeen philosophers explore these and other questions that relate to what it means to be a man, including questions about pornography and homosexuality. New essays look at masculinity and violence, research on differences between men's and women's brains, impotence, sexual ambiguity, and whether black men have a moral duty to marry black women.
Section: xx, 236 pages
Keywords: LGBTQIA2+; approches et analyses; cours; discipline; discours dominant; histoire et politique; masculinité; masculinités; patriarcat; philosophie; premier cycle; rapports sociaux de sexe; sciences humaines; soc2014; systèmes d'oppressions; thématiques